Makna Kritus sebagai Kepala Gereja Menurut Efesus 5:22-23 dan Implikasinya bagi Pembangunan Tubuh Kristus - Juanda Yulianus (Sekolah Tinggi Teologia Kerusso Indonesia, 2022)
Christ is the head of the church because believers believe in Christ. In His plan to give eternal life, Christ played a role in the establishment and growth of His church to the present day so that the doctrine of the person of Jesus or Christology became very important to Christians. A healthy church is one that grows according to His will and grows toward Him. Christ's work for today's church makes it experience a consistent dynamic of growth. Christ's presence in the church is His activeness in expressing his function and duty to the church as His own people. In Christ's role for His church, it shows Christ's relationship with the church itself.